Modelo de gestión por procesos para el área académica en la Escuela de Administración de Empresas y Marketing de la Universidad Politécnica Estatal del Carchi, año 2014 - López Cadena, Julio Iván (2014)
The Ecuadorian education system is undergoing significant structural changes that are enabling the authorities of the universities to change their management approach, from a traditional ad-ministration, bureaucratic, go to a results-based management and process-focused, all seeks to look at continuous improvement and ensure quality of education over time. The system approach to process management raised at school administered-ing business and marketing is based on the model of Excellence Quality Malcolm Baldrige, and Iso 9001: 2008 for the implementation of the management system quality. The field study raised in the university community identified the need to have a system of pro-cess management in the school of business administration and marketing, which contribute to the continuous improvement and organizational development, and thus ensure the survival of the institution over time. The proposed process management system in school business administration and marketing was found divided into five major components: 1.A process map which was the starting point to organize the processes by management, operating and support types . 2. Processes tab where all the information needed to further substantiate the manual process was compiled. 3 The de-tails of the processes included: objective, scope, responsible, detail and document each of the academic management procedures in the school of business administration and marketing. 4 Each procedure was based process with a flowchart. 5 And finally allowed process indicators that measure the efficiency and procedures regarding compliance with RBM run.